The Role of Social Media in the Implementation of Sustainable Marketing: Consumer Behavior, Brand Engagement, and Green Consumption - Gregurec, Iva; Kutnjak, Ana; Kuštelega, Magdalena (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
Many companies integrate sustainable business practices into their marketing strategies, enhancing supply chain management, product development, and decision-making. The growing use of social media has facilitated green advertising, enabling knowledge exchange and awareness. This study examines the impact of social media on sustainable marketing, focusing on consumer behavior, brand engagement, and green consumption. It aims to determine how digital technologies, social media actors, and interactions support sustainable marketing within companies. A literature review of Scopus and Web of Science databases identifies key trends and empirical findings in the researched field. Results highlight that social media promotes eco-friendly products, raises environmental awareness, and fosters engagement through influencer marketing. Findings suggest that sustainable brand positioning via social media enhances consumer trust and loyalty, while digital marketing interactions significantly influence green purchasing decisions. Additionally, the accessibility and interactivity of social media content shape consumer attitudes toward sustainable brands. Study limitations include the exclusive use of two databases and a restricted publication timeframe. Practical implications suggest that companies should strategically leverage social media to educate and engage consumers in sustainability. This research contributes to sustainable marketing by illustrating how digital technologies drive environmental, social, and economic responsibility while fostering consumer participation.